Identifying Healthcare Professional Roles in Developing Palliative Care: A Mixed Method - Alonazi, Wadi B. (Frontiers in Public Health, 2021)
Background: Creating a holistic approach in healthcare services is the ultimate aim of integration healthcare system. Conceptually, health policy makers constantly have called for optimal operations of healthcare organizations through engaging healthcare professionals’ paradigm. The objective of this study is to explore and address the under recognized role of healthcare professionals to maintain effective palliative care programs in safe and high-quality of care. Practically, the potential steps towards further effective mobilization of cohesive palliative care centers reform were derived from healthcare practitioners’ experience. Methods: In a balanced assignment sampling, 28 healthcare professionals were selected from a large group of policy-makers team concerned in setting priorities for the Ministry of Health in Saudi Arabia (Jan- Feb 2020). To document the major factors affecting reform success, three relevant focus groups were simultaneously formulated, under the supervision of three independent health researchers. Then, two focus groups had been sub-grouped to prioritize the results; each one consisted of six healthcare administrators. Data were transcribed, coded, and further analyzed; finally, themes were extracted based on the codes. Findings: The initial results incorporated 36 key factors in building effective and sustained palliative healthcare centers. The domains were feasible and practical as they homogeneously patterned within cultural change. The Spearman correlation matrix showed significant relationships between some successful factors (P<0.01 and P<0.05). Health administrators contributed to create four themes: quality of care, effective management, institute of medicine criteria, and health governance. Conclusions: To build effective palliative care centers, the findings take steps towards a comprehensive periodic assessment of the situation, especially in terms of managerial implications and quality of care.